Thinking about Place and Culture: An American Geographer in Catalunya - Gade, Daniel W. (Treballs de la Societat Catalana de Geografia, 2008)
In this essay on the geography of the heart, I use my experience in Catalunya to elaborate how geographers discover place and how a foreign encounter can transform ones thinking. Intellectual inspiration in this trajectory has come from Goethe (self-aware traveler with an open mind); Herder (originator of the notion of cultural-linguistic diversity), A. Humboldt (scientist curious about foreign lands); Royce (philosopher of the periphery); and Sauer (maestro of a cultural historical approach to geography). Learning about place at three scales has been a process of discovery illuminated by revisitation, reflection, and comparison. The small city of Olot has offered perspectives on pedestrianoriented urban living; the comarca of La Garrotxa has stimulated thinking about the logic of an environmenteally coherent micro-region; and Catalunya has provided an example of how solidarity, a sense of the past, but also the conjuncture of the Zeitgeist, have led to an extraordinary cultural resurgence.